A study of river management models in Malaysia. - Chan, Ngai Weng (Universiti Sains Malaysia, 2013)
Rivers provide water supply, irrigation, transportation, food, and other natural functions. In Malaysia, rapid development in recent decades has overstressed river systems leading to inadequate water supply, pollution and floods. Disintegrated management via the sectoral approach was found to have given rise to ineffective river management in most states. Disputes between various levels of government, competition between different government bodies and the low salience given to river conservation exacerbates the problem. This study is based on a survey of river users, government officers and NGO managers. Study methods include institutional analysis, river mapping, secondary data and questionnaire survey. It found that there is not one existing river management model that is effective. Most states manage rivers poorly via the top-down government-centric model without involving the stakeholders.